2021
DOI: 10.3390/ijerph18041634
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Activities of Daily Living in Stroke Patients with Motion Machine Learning Algorithms: A Pilot Study

Abstract: Measuring activities of daily living (ADLs) using wearable technologies may offer higher precision and granularity than the current clinical assessments for patients after stroke. This study aimed to develop and determine the accuracy of detecting different ADLs using machine-learning (ML) algorithms and wearable sensors. Eleven post-stroke patients participated in this pilot study at an ADL Simulation Lab across two study visits. We collected blocks of repeated activity (“atomic” activity) performance data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Are systems which aim to identify specific movements of rehabilitation of the patients and differentiate between them for record and monitoring purposes [41][42][43][44][45][46][47][48][49][50][51], in this category researchers monitored Activities of Daily Living (ADL) [75] and they most frequently covered detecting general activities like standing, sitting, lying, standing up, sitting down [42,44,47,48,50], performing kitchen tasks like making a drink, chopping food [42] and other routine activities like making the bed, reading and lacing shoes [48], folding, sweeping and brushing teeth [46,48,49]. Other researchers covered activities for specific body parts like recognising different hand gestures [41], arm gestures [43] and some exercises to strengthen shoulders, and arms [48].…”
Section: Activity Recognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Are systems which aim to identify specific movements of rehabilitation of the patients and differentiate between them for record and monitoring purposes [41][42][43][44][45][46][47][48][49][50][51], in this category researchers monitored Activities of Daily Living (ADL) [75] and they most frequently covered detecting general activities like standing, sitting, lying, standing up, sitting down [42,44,47,48,50], performing kitchen tasks like making a drink, chopping food [42] and other routine activities like making the bed, reading and lacing shoes [48], folding, sweeping and brushing teeth [46,48,49]. Other researchers covered activities for specific body parts like recognising different hand gestures [41], arm gestures [43] and some exercises to strengthen shoulders, and arms [48].…”
Section: Activity Recognitionmentioning
confidence: 99%
“…Over the past few years, effort has been put into developing unobtrusive, effective and objective motion-modeling systems, taking advantage of the progress made in the sensor technology which became more compact and more power-efficient [83]. All the included works utilised IMUs for the data acquisition [42][43][44][45][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61][65][66][67][68][69][70]63,[71][72][73][74]64]. IMUs are devices that combine linear acceleration from accelerometer and the angular turning rates from gyroscopes [84].…”
Section: Wearable Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensation is essential for safety even if there is adequate motor recovery [11]. Findings particularly suggest the importance of somatosensory function after stroke for recovery of precision grip force control [12], safety and dexterity in the paretic hand [13] and functional independence in activities of daily living (ADL) [14,15]. Current findings showed that active and passive sensory retraining may be an effective intervention for improving the light touch threshold of the hand, dexterity, upper extremity (UE) motor function [10,16] to improve the activity of daily living in stroke patients with impaired sensory motor abilities [17].…”
Section: Introductionmentioning
confidence: 99%